Simultaneous Sampling of Tissue Oxygenation and Oxygen Consumption in Skeletal Muscle - Nugent, William H. (Microvasc Res, 2015)
Under physiologic conditions, microvascular oxygen delivery appears to be well matched to oxygen consumption in respiring tissues. We present a technique to measure interstitial oxygen tension (P(ISF)O(2)) and oxygen consumption (VO(2)) under steady-state conditions, as well as during the transitions from rest to activity and back. Phosphorescence Quenching Microscopy (PQM) was employed with pneumatic compression cycling to achieve 1 to 10 Hz sampling rates of interstitial PO(2) and simultaneous recurrent sampling of VO(2) (3/min) in the exteriorized rat spinotrapezius muscle. The compression pressure was optimized to 120–130 mmHg without adverse effect on the tissue preparation. A cycle of 5 s compression followed by 15 s recovery yielded a resting VO(2) of 0.98 ± 0.03 ml O(2)/100cm(3) min while preserving microvascular oxygen delivery. The measurement system was then used to assess VO(2) dependence on P(ISF)O(2) at rest and further tested under conditions of isometric muscle contraction to demonstrate a robust ability to monitor the on-kinetics of tissue respiration and the compensatory changes in P(ISF)O(2) during contraction and recovery. The temporal and spatial resolution of this approach is well suited to studies seeking to characterize microvascular oxygen supply and demand in thin tissues.